2019
DOI: 10.1177/0363546519859855
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation of Aggregates of Autologous Synovial Mesenchymal Stem Cells for Treatment of Cartilage Defects in the Femoral Condyle and the Femoral Groove in Microminipigs

Abstract: Background: Previous work has demonstrated that patients with cartilage defects of the knee benefit from arthroscopic transplantation of autologous synovial mesenchymal stem cells (MSCs) in terms of magnetic resonance imaging (MRI), qualitative histologic findings, and Lysholm score. However, the effectiveness was limited by the number of cells obtained, so large-sized defects (>500 mm2) were not investigated. The use of MSC aggregates may enable treatment of larger defects by increasing the number of MSCs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 57 publications
(71 reference statements)
0
21
0
Order By: Relevance
“…195 Intra-articular injection of SMSCs could markedly promote cartilage repair and be used to treat joint-related diseases, including OA, in experimental animal models. [196][197][198][199] Recently, several studies revealed that exosomes derived from SMSCs could effectively promote cartilage regeneration and attenuate OA progression. 122,195,200 Tao et al reported that SMSC-derived exosomes could induce the proliferation and emigration of articular chondrocytes in a Wnt5a/Wnt5b/YAPdependent manner.…”
Section: Ultrafiltrationmentioning
confidence: 99%
“…195 Intra-articular injection of SMSCs could markedly promote cartilage repair and be used to treat joint-related diseases, including OA, in experimental animal models. [196][197][198][199] Recently, several studies revealed that exosomes derived from SMSCs could effectively promote cartilage regeneration and attenuate OA progression. 122,195,200 Tao et al reported that SMSC-derived exosomes could induce the proliferation and emigration of articular chondrocytes in a Wnt5a/Wnt5b/YAPdependent manner.…”
Section: Ultrafiltrationmentioning
confidence: 99%
“…Nakamura et al [75] injected fluorescently labeled allogeneic SM-MSCs suspension into the osteochondral defect in pigs; 4 weeks later, they found the osteochondral defect was filled with cartilage matrix. Kondo et al [76] selected autologous SM-MSCs aggregates to investigate whether SM-MSCs could successfully repair the cartilage defects in microminipigs in the medial femoral condyle and femoral groove. Their results showed that the transplantation of SM-MSC aggregates promoted the regeneration of the articular cartilage in the medial femoral condyle of microminipig but not in the femoral groove, suggesting that the site of cartilage defect may also affect the cartilage repair ability of stem cells.…”
Section: Study Of Sm-mscs In Cartilage Repairmentioning
confidence: 99%
“…Studies have shown that SMSCs from OA patients can repair cartilage through allogenic tissue-engineered constructs in both in vitro and in vivo models. In experimental animal models, the injection of SMSCs into the joint cavity achieved a similar effect (Kondo et al, 2019;Enomoto et al, 2020;Dragoo et al, 2012). Infrapatellar fat pad (IPFP), a column of fat tissue located behind the patella, and synovium are involved in the occurrence and development of intra-articular diseases, such as OA (Favero et al, 2017).…”
Section: Mesenchymal Stem Cellsmentioning
confidence: 99%